2014
DOI: 10.1002/cphc.201301030
|View full text |Cite
|
Sign up to set email alerts
|

From the Molecular Structure to Spectroscopic and Material Properties: Computational Investigation of a Bent‐Core Nematic Liquid Crystal

Abstract: We present a computational investigation of the nematic phase of the bent-core liquid crystal A131. We use an integrated approach that bridges density functional theory calculations of molecular geometry and torsional potentials to elastic properties through the molecular conformational and orientational distribution function. This unique capability to simultaneously access different length scales enables us to consistently describe molecular and material properties. We can reassign (13)C NMR chemical shifts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
(231 reference statements)
5
10
1
Order By: Relevance
“…It would appear that the ‘average’ A131 molecules belong to the ( Γ 1 , Γ 4 ) variety. This is consistent with the recent finding based on a molecular field theory that the molar fraction of ( Γ 1 , Γ 4 ) amounts to 90% at 395 K . As seen in the figure, the twist angles of rings ‘b’, ‘d’, and ‘e’ are relatively insensitive to the temperature over the nematic range, while despite rather large scatterings, ξ a of ring ‘a’ seems to show a pronounced change.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It would appear that the ‘average’ A131 molecules belong to the ( Γ 1 , Γ 4 ) variety. This is consistent with the recent finding based on a molecular field theory that the molar fraction of ( Γ 1 , Γ 4 ) amounts to 90% at 395 K . As seen in the figure, the twist angles of rings ‘b’, ‘d’, and ‘e’ are relatively insensitive to the temperature over the nematic range, while despite rather large scatterings, ξ a of ring ‘a’ seems to show a pronounced change.…”
Section: Resultssupporting
confidence: 92%
“…As seen in the figure, the twist angles of rings ‘b’, ‘d’, and ‘e’ are relatively insensitive to the temperature over the nematic range, while despite rather large scatterings, ξ a of ring ‘a’ seems to show a pronounced change. Recent DFT calculations indicated that ring ‘a’ has a wider angular distribution, as the potential barrier for rotations with respect to ring ‘b’ is low. Here, we see in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Rhombic polar order-parameters have been invoked in the context of twist-bend nematic phases. 39 However, they have been associated with the conical angle and the pitch of the medium, rather than potentials formed of odd- L terms of eq 2. Potentials given by the L = 1, K = 0 term have been used to analyze dielectric relaxation of ferroelectric systems, 40 to treat electric-field-implied polar order, 41 and interpret the orientation of asymmetric paramagnetic molecules in strong magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…It seems conceivable that a N x phase can appear through stabilizing a uniaxial nematic system with local biaxial and polar cybotactic clusters by suitable purturbations such as surface treatment or an external field [79]. Ferrarini and coworkers have recently reinterpreted the temperature behaviors of 13 C chemical shifts previously reported in both nematic phases [287] using a statistical approach [293]. All Γ (Γ 1 ÀΓ 4 ) conformers together with chain conformers using Monte Carlo sampling were considered in the SI model, which used an adjustable parameter E to reflect the orienting strength of the nematic environment.…”
Section: Conformational Problem Of Bcms: a Case Studymentioning
confidence: 94%